Stakeholder involvement through a partnership model for sustainable tourism development - Rahmawati, Rita; Apriliani, Afmi; Sastrawan, Berry (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to map stakeholder involvement in tourism developed through a public-private partnership and analyze the factors that hinder tourism development. This research used a descriptive method with a quantitative and qualitative approach, with an analysis unit of the Sukabumi Regency Tourism Office Employee. Sample selection using a purposive sampling technique. Data collection techniques used were questionnaires, in-depth interviews, and FGDs. The research results showed that stakeholder engagement and partnership implementation in tourism development have not been optimal. Although the average results of respondents' answers obtained a score of 4.0 included in the "good" category; there are factors that hinder tourism development, including limited quantity and quality of human resources in the tourism sector; the still low accessibility and infrastructure of tourism; the absence of specific guidelines in stakeholder engagement and tourism development partnership models. (3) Results of FGD recommended the need for institutional strengthening of the regional apparatus organization (OPD), the preparation of guidelines for exclusive partnership, roles, and responsibilities through capacity building, improvement of budget, infrastructure improvements, and increased accessibility.